THE EFFECTIVENESS OF ENGLISH COMIC AS MEDIA TO IMPROVE READING COMPREHENSION OF NARRATIVE TEXT AT THE SECOND YEARS STUDENTS OF SMP NEGERI 1 BARRU - Dg Tallasa; Ummi Khaerati Syam; Muh. Arief Muhsin (FKIP Unismuh Makassar, 2021)
This research aimed to find out the influence of English Comic as Mediaon students reading comprehension that focus on level of literal and interpretative of comprehension. The researcher applied pre-experimental method with one group pre-test and post-test. The sample of this research was class VIII A of SMP NEGERI 1 BARRU which consisted of 30 students. The sample was taken by using purposive sampling method. The research findings showed that the second grade of SMP NEGERI 1 BARRU had Fair score in pre-test. After given treatment their reading comprehension was significantly improved. The result of the research was the mean score of pre - test in Literal (main Idea) score of pre-test was 58.6 and post-test was 86.56. In sequence of detail the score of pre-test was 56.4 and post-test was 92.6 with t-test value Literal is greater than t-table (13.26 > 2.45). Mean score of interpretative in pre - test was 63.63 and post-test was 82 with the t-test value is greater that t-table (8.34 >2.45). The result of calculating t-test of the indicators in the students t-test (Literal and Interpretative) was greater than t-table 21.60 > 2.45. it means that there was significance different between before and after giving the treatment. It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It was concluded that the use of OKRE Influence the students’ reading comprehension.